(untitled) (Research, Society and Development, 2025)
Sisal (Agave sisalana Perrine) is a plant from the Asparagaceae family that has become a valuable source of income for numerous families in the state of Bahia. Its cultivation is mainly intended for the creation of artisanal products, which stimulate the local economy. However, its processing generates waste materials that often lack a defined use but can be repurposed as animal feed. In this context, the present study aimed to evaluate the increase in protein content of the sisal coproduct following semi-solid fermentation over periods of 8, 24, 32, and 48 hours, using the fungi Lentinus tigrinus, Trametes villosa, and the yeast Saccharomyces cerevisiae. A significant variation in crude protein (CP) levels was identified for each microorganism applied (p<0.05), starting in the initial hours of the experiment. The most substantial increase in protein content occurred at 48 hours of fermentation in all treatments. The substrate inoculated with L. tigrinus showed a 34.4% increase, followed by T. villosa with 33.3%, and S. cerevisiae with 30.2%, when compared to the untreated residue. The results underwent regression and analysis of variance (ANOVA), and the coefficients of determination (R²) for the respective microorganisms over time were 0.8404, 0.9956, and 0.967, indicating a strong fit between the model and the observed data. Additionally, reductions in lignin, hemicellulose, neutral detergent fiber (NDF), and acid detergent fiber (ADF) contents were noted after 48 hours, confirming this as the most suitable time point for assessing the parameters analyzed.